The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s0263574717000571
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of in-field motion capture approaches for body kinematics measurement in construction

Abstract: SummaryDue to physically demanding tasks in construction, workers are exposed to significant safety and health risks. Measuring and evaluating body kinematics while performing tasks helps to identify the fundamental causes of excessive physical demands, enabling practitioners to implement appropriate interventions to reduce them. Recently, non-invasive or minimally invasive motion capture approaches such as vision-based motion capture systems and angular measurement sensors have emerged, which can be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Data synchronisation was occasionally reported as part of the pre-processing stage and included in the data fusion algorithm [ 24 , 34 , 36 ], but technical details were frequently omitted in the reviewed studies [ 27 , 28 ]; yet, when the synchronization strategy was reported, a master control unit [ 36 , 50 , 51 , 54 ] or a common communication network [ 15 , 31 , 67 ] were used. Different sampling rates of data streams were addressed by linear interpolation and cross-correlation [ 73 ] techniques, or by introducing a known event that triggers all the sensors [ 29 , 47 , 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data synchronisation was occasionally reported as part of the pre-processing stage and included in the data fusion algorithm [ 24 , 34 , 36 ], but technical details were frequently omitted in the reviewed studies [ 27 , 28 ]; yet, when the synchronization strategy was reported, a master control unit [ 36 , 50 , 51 , 54 ] or a common communication network [ 15 , 31 , 67 ] were used. Different sampling rates of data streams were addressed by linear interpolation and cross-correlation [ 73 ] techniques, or by introducing a known event that triggers all the sensors [ 29 , 47 , 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two works also used the Oculus Rift virtual reality headset to remotely assess industrials locations and control robotic elements [ 39 , 43 ]. The tracking accuracy of the developed systems was directly assessed against gold-standard MoCap systems (e.g., Vicon or Optotrack; Table 8 , in bold) in six works [ 14 , 15 , 55 , 59 , 73 , 77 ], while the classification or identification accuracy of a process was frequently evaluated with visual inspection of video or phone cameras [ 15 , 29 , 36 , 44 , 60 , 63 , 69 ]. A thorough diagram showing the connections between type of industry, application and MoCap system, for each considered study is also presented on Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 3, most of the three-dimensional scanned models of the human body are expensive and require a long time to do postprocessing, and the initial model obtained from the scan because there is no joint structure information, in the posture estimation before the need to set the skeletal structure, for its skin, etc. is increases the initial model to a certain extent [17].…”
Section: False Motion Recognition and Visual Algorithm Matchingmentioning
confidence: 99%